PENGARUH PENAMBAHAN SARI KACANG HIJAU (Vigna radiata) TERHADAP KARAKTERISTIK KIMIA DAN ORGANOLEPTIK HARD CANDY AIR KELAPA (Cocos nucifera L.) - Wokas, Chichilia; Mandey, Lucia Cecilia; Oessoe, Yoakhim Y. E.; Lalujan, Lana E.; Mamuaja, Christine F.; Tuju, Thelma D. J. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
The purpose of this study was to evaluate the effect of the addition of mung bean juice on the level of liking, hardness, and analyze the water content, ash content, and reduced sugar content of coconut water hard candy. The research method used is the Completely Randomized Design (CRD) method with 5 treatments where A. The addition of 10% mung bean juice, B. The addition of 15% mung bean juice, C. The addition of 20% mung bean juice, D. The addition of 25% mung bean juice, E. The addition of 30% mung bean juice then measured the level of liking test, hardness test, water content, ash content and reducing sugar content. The results showed that coconut water hard candy with the addition of mung bean juice had no significant effect on the level of liking test on taste 4.76 (rather like) - 5.68 (like), aroma 4.56 - 5.36 (rather like), color 4.56 - 5.36 (rather like), and had a significantly different effect on the hardness test with an average value of 3.88 (rather hard) - 5.16 (neutral). The results showed that coconut water hard candy with the addition of nut juice had a significantly different effect and had an average value of water content of 0.60% - 2.44%, ash content of 0.32% - 1.19%, and the test of reducing sugar content showed that it had a not significantly different effect which ranged from 1.38% - 2.18%.